2021
DOI: 10.1002/jcc.26491
|View full text |Cite
|
Sign up to set email alerts
|

The CH···HC interaction in biphenyl is a delocalized, molecular‐wide and entirely non‐classical interaction: Results from FALDI analysis

Abstract: In this study we aim to determine the origin of the electron density describing a CHÁÁÁHC interaction in planar and twisted conformers of biphenyl. In order to achieve this, the fragment, atomic, localized, delocalized, intra-and inter-atomic (FALDI) decomposition scheme was utilized to decompose the density in the inter-nuclear region between the ortho-hydrogens in both conformers. Importantly, the structural integrity, hence also topological properties, were fully preserved as no 'artificial' partitioning of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 44 publications
4
15
0
Order By: Relevance
“…In the biaryl types of systems, mainly for the biphenyl (either simple or substituted), which is capable of exhibiting conformational preferences, numerous reports exist in the literature. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][36][37][38][39][40][41][42][43][44][45] It is well known that a simple (unsubstituted) biphenyl is twisted in the ground state (gas phase). [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][36][37][38][39][40][41]…”
Section: Conformational Preferences In Biaryl Systemsmentioning
confidence: 99%
“…In the biaryl types of systems, mainly for the biphenyl (either simple or substituted), which is capable of exhibiting conformational preferences, numerous reports exist in the literature. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][36][37][38][39][40][41][42][43][44][45] It is well known that a simple (unsubstituted) biphenyl is twisted in the ground state (gas phase). [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][36][37][38][39][40][41]…”
Section: Conformational Preferences In Biaryl Systemsmentioning
confidence: 99%
“…A multi-centric, 37,45,47 multi-orbital, 35,43,47 and molecular-wide 46 nature of a "diatomic" interaction strongly questions not only an orthodox concept of a chemical 2-atom bond in a multi-nuclei environment but the chemical bond unicorn altogether. Many molecules or their fragments are highly "flexible" and, due to structural rearrangement, form numerous and comparable in stability 3D constellations of nuclei (conformers or isomers) with an intact major network of diatomic interactions (classical covalent bonds) but very different set of intramolecular interactions between classically nonbonded atoms.…”
Section: Famsec-based Methods In Exploring the Molecular-wide And Den...mentioning
confidence: 99%
“…This function accounts for the rate of change of facilitating (concentrating ED) relative to hindering (depleting ED) factors in the vicinity of either a CP or MDP. Importantly, the CP ( r ) function can be used: (1) in any internuclear region, (2) at any level of theory, (3) for attractive and repulsive (non)bonded interactions, and (4) in (non)equilibrium structures 46 . It can be also applied equally well using combined concentrating and depleting contributions obtained either from MO‐based 35 or FALDI‐based 45 methods.…”
Section: New Tools In Exploring and Understanding Chemical Bondingmentioning
confidence: 99%
See 1 more Smart Citation
“…[21] In addition, using the energy partitioning by the interacting quantum atoms method (IQA) into atomic and interatomic contributions, it has been found that as the molecule goes to the planar transition state there is a net increasing attraction between the H ortho and H' ortho atoms that is dominated by the exchange interaction energy. [22] Notwithstanding this, as emphasized by Bates et al, [23] to explain the rotation barrier, the energy changes in the whole molecule have to be considered: the increase of atomic self-energies and less favorable CÀ C interactions during rotation. In another study, using the non-covalent interaction (NCI) index, [24] Laplaza et al [25] also concluded that the H⋯H interactions in planar BP are of attractive nature.…”
Section: (A) It Is Consideredmentioning
confidence: 99%